The Link between Autoimmunity and Lymphoma: Does NOTCH Signaling Play a Contributing Role? - Kuksin, Christina Arieta; Minter, Lisa M. (Frontiers in Oncology, 2015)
An association between certain autoimmune conditions and increased risk of developing lymphoma is well documented. Recent evidence points to NOTCH signaling as a strong driver of autoimmunity. Furthermore, a role for NOTCH in various lymphomas, including classical Hodgkin lymphoma, non-Hodgkin lymphoma, and T cell lymphoma has also been described. In this mini-review we will outline what is known about involvement of NOTCH signaling in those autoimmune conditions, such as rheumatoid arthritis and primary Sjörgren’s Syndrome, which show an increased risk for subsequent diagnosis of lymphoma. Furthermore, we will detail what is known about the lymphomas associated with these autoimmune conditions and how aberrant or sustained NOTCH signaling in the immune cells that mediate these diseases may contribute to lymphoma.